The Function of the Basuh Lantai Tradition for the Daik Village Community - Panca Dwi Kora; Daryusti Daryusti (Universitas Negeri Medan, 2024)
Culture is the characteristic identity of any group or community, which is upheld within its boundaries. Culture as a product of human thought records community traditions in various ceremonies such as births, funerals, agricultural rituals and musical performances. One of the ingrained traditions is the Washing the Floor custom in Daik Village, Lingga Regency, Riau Islands Province, which is carried out before giving birth. This qualitative research conducted in Daik Village immersed researchers in the local community, aiming to understand the social significance and evolution of the Basuh Floor tradition. By demonstrating solidarity and actively participating with the locals, the researcher aims to gather accurate information for this study. The results reveal the tradition's connection to animist beliefs and its role in protecting against mystical forces. Despite modernization, the decline of these traditions reflects changing attitudes towards childbirth practices and health care. This study underscores the importance of preserving cultural heritage amidst societal change. Despite its decline, the Basuh Floor tradition remains an integral part of the cultural identity of Daik Lingga Village and the Riau Islands as a whole. It serves as a symbol of cultural continuity and resilience, reminding the community of their heritage and providing a sense of belonging and identity. Additionally, it underscores the importance of understanding and preserving cultural practices, not only for their symbolic value but also for their role in maintaining social cohesion and collective memory.